Judiciary of the 21st century: How the literature suggests a new way to evaluate the judiciary using the perception of citizens - Costa, C. A.; Laureano, R. M. S.; Afonso, C. W. (Revista Electrónica de Direito Processual, 2024)
It is essential to implement a new way of evaluating the judiciary that considers the perception of citizens, particularly in the 21st century, where there is a pressing need to involve society in discussions about improving public services. In addition to utilizing information from specialists such as lawyers, public servants, and judges, citizens can provide a new perspective that can help enhance the quality of judiciary services. The objective of this article is to present the state-of-the-art on the subject of "Judiciary Evaluation" and how citizens' perceptions can be integrated into this process. The findings of the theoretical study reveal a lack of research on citizen and judiciary evaluation, emphasizing the importance of including citizens in the judiciary evaluation model.